IMPLEMENTASI PEMBELAJARAN DARING PADA MASA PANDEMI COVID-19 DAN DAMPAKNYA - SITI NUR ANISAH (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
The purpose of this article is to understand, explain, and analyze the implementation of online learning during the COVID-19 outbreak and its effects. The research design used literature study. The necessary data is collected through text studies, then analyzed using content analysis techniques. The results of the literature study, it was found that during the COVID-19 pandemic, learning activities in training were focused on fulfilling the health stándar through online development methods. The improvement of trainee competence in online learning are 3 basic competencies (knowledge, attitudes and behavior) based on digital literacy. Reducing the impact of online learning can be done by fulfilling human resources who understand and are skilled in the use of information technology, provision of adequate infrastructure, adequate internet access, use of media and tools to achieve these online learning goals. ABSTRAKTujuan penulisan artikel ini adalah untuk memahami, menjelaskan, dan menganalisis implementasi pembelajaran daring pada masa pendemi COVID-19 dan dampaknya. Penulisan artikel ini menggunakan studi literatur. Data yang diperlukan dihimpun melalui kajian teks, selanjutnya dianalisis menggunakan teknik analisis isi. Dari hasil studi literatur didapatkan bahwa selama masa pandemi COVID-19 kegiatan pembelajaran dalam pelatihan difokuskan untuk memenuhi stándar kesehatan yaitu melalui metoda pembelajaan daring. Peningkatan kompetensi peserta pelatihan dalam pembelajaran daring adalah 3 kompetensi dasar (pengetahuan, sikap dan perilaku) berbasis literasi digital. Pengurangan dampak dari pembelajaran daring dapat dilakukan dengan pemenuhan sumber daya manusia yang memahami dan terampil dalam penggunaan teknologi informasi, penyediaan sarana-prasarana yang memadai, akses internet yang cukup, penggunaan media dan alat bantu untuk mencapai tujuan pembelajaran daring tersebut.